Linking appraisal to behavioral flexibility in animals: implications for stress research - Faustino, Ana I.; Oliveira, Gonçalo A.; Oliveira, Rui F. (Frontiers in Behavioral Neuroscience, 2015)
In fluctuating environments, organisms require mechanisms enabling the rapid expression of context-dependent behaviors. Here, we approach behavioral flexibility from a perspective rooted in appraisal theory, aiming to provide a better understanding on how animals adjust their internal state to environmental context. Appraisal has been defined as a multi-component and interactive process between the individual and the environment, in which the individual must evaluate the significance of a stimulus to generate an adaptive response. Within this framework, we review and reframe the existing evidence for the appraisal components in animal literature, in an attempt to reveal the common ground of appraisal mechanisms between species. Furthermore, cognitive biases may occur in the appraisal of ambiguous stimuli. These biases may be interpreted either as states open to environmental modulation or as long-lasting phenotypic traits. Finally, we discuss the implications of cognitive bias for stress research.